2013
DOI: 10.1179/2045772313y.0000000162
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcomes among youth with spinal cord injury by neurological impairment

Abstract: Objective: Examine psychosocial outcomes of youth with spinal cord injury (SCI) as a function of neurological level (paraplegia/tetraplegia) and severity (American Spinal Injury Association (ASIA) Impairment Scale (AIS)). Design: Survey research. Setting: Three pediatric SCI specialty centers in the USA. Participants: Youth with SCI ages 5-18 with neurological impairment classifications of: tetraplegia AIS ABC (tetraplegia ABC), paraplegia AIS ABC (paraplegia ABC), or AIS D. Outcome Measures: Children's Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…These researchers noted the counterintuitive nature of their findings and recommended further investigation to better understand this association, proposing that individuals with incomplete injuries are provided with less support and that their symptoms of fatigue and frustration may be more easily overlooked than are the more obvious symptoms of those with complete injuries. More recently, Riordan et al (2015) found that outcomes of youth with AIS D injuries were less favorable than youth with AIS A/B/C injuries as related to social quality of life, even with similar levels of participation; this study had a relatively small number of individuals with AIS D injuries, and the researchers indicated that future studies may shed further light on this relationship.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…These researchers noted the counterintuitive nature of their findings and recommended further investigation to better understand this association, proposing that individuals with incomplete injuries are provided with less support and that their symptoms of fatigue and frustration may be more easily overlooked than are the more obvious symptoms of those with complete injuries. More recently, Riordan et al (2015) found that outcomes of youth with AIS D injuries were less favorable than youth with AIS A/B/C injuries as related to social quality of life, even with similar levels of participation; this study had a relatively small number of individuals with AIS D injuries, and the researchers indicated that future studies may shed further light on this relationship.…”
Section: Introductionmentioning
confidence: 84%
“…Other possible reasons why those with AIS D SCI may present with unexpected psychological challenges include age (tend to be older), morbidities (due to older age), unique pain characteristics, social support (do not as often require caregivers), attitudes of others (given the less visible nature of impairments), or selfappraisals (Mignogna, Christie, Holmes, & Ames, 2015). Riordan et al (2015) noted that youth with AIS D injuries tended to have the highest level of overall anxiety and depression in their study, and they proposed that youth with AIS D injuries may not feel a sense of belonging either with other youth with SCI or with able-bodied youth, which could lead to negative self-perceptions and psychosocial consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk of depression was increased in those who were unemployed throughout the study. Employment rates were higher in participants who were women, had advanced degrees, were married, and had less severe neurological impairment [75,77]. Occurrence of secondary health conditions such as severe urinary tract infections, autonomic dysreflexia, spasticity, or another chronic health condition decreased the odds of employment, suggesting value in targeted interventions for these conditions and in educational preparation for employment.…”
Section: Employmentmentioning
confidence: 91%
“…Up to 62 % of children with SCI reported no involvement in organized community activities [76]. Among youth with AIS A, B, and C, those with paraplegia had higher participation rates than youth with tetraplegia [77].…”
Section: Participationmentioning
confidence: 99%